Miscellany/Mélanges - Besterman, T (Voltaire Foundation, 2017)
Theodore Besterman, Additions and corrections to the definitive edition of Voltaire's correspondence. IV: vols. i-xxxiv (Voltaire 85-118) David Williams, Voltaire on the sentimental novel Nancy Senior, The Structure of Zadig Patrick Henry, A Different view of Voltaire's controversial Tout en dieu Samuel S. B. Taylor, The Duke and duchess of Grafton with Voltaire: notes on unrecorded silhouettes by Jean Huber with a plate Samuel S. B. Taylor, Voltaire's marginalia: a preview of the forthcoming edition, with four plates English Showalter, Jr, Sensibility at Cirey: Mme Du Châtelet, Mme de Graffigny, and the Voltairomanie Jeroom Vercruysse, Lettre de Henri Rieu sur les derniers jours de Voltaire Ruth P. Thomas, Les Bijoux indiscrets as a laboratory for Diderot's later novels John Renwick, Encore des précisions nouvelles sur les débuts de Beaumarchais